The UK Biological Security Strategy: an introduction and inspiration - Yuan LIU; Shaozheng YANG; Jiamin LONG; Xuelian WU; Xinya XIE; Xiong LIU; Jinpeng GUO; Yong CHEN; Changjun WANG (Editorial Office of Chinese Journal of Public Health, 2024)
In recent years, the emergence of novel biological threats has brought biosecurity issues to the forefront of societal concerns. The United Kingdom established the UK Biological Security Strategy in 2018, and after revisions, a new version was published in June 2023. The strategy presents the UK's new vision, mission, outcomes, and plans, and provides action plans from four perspectives: understanding, preventing, detecting, and responding to major biological threats to protect the UK's national interests and enhance biosecurity emergency preparedness and response capabilities. This article introduces the main contents and framework of the 2023 UK Biosecurity Strategy in detail, and reflects on its implications to provide a reference for the construction and development of China's biosecurity strategy.